2002
DOI: 10.1108/00035590210419362
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate stress corrosion cracking in waste heat recovery boilers

Abstract: Waste Heat Recovery Boilers (WHRB's) enhance the thermal efficiency of gas turbine power generating plants by capturing the heat from the exhaust gas and utilising it to raise steam for increased electricity production or district heating. Under normal conditions the exhaust gas from the turbine is cooled from around 5508C to 808C. Care is taken that condensation will not occur in the cooler parts of the boiler. Nevertheless, during normal operation, dry ammonium nitrate deposits can be formed in the WHRB. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In this range of wall temperatures usual operating conditions would not produce water vapor condensation between outer steel casing and refractory bricks. In addition to pure water vapor, the nitric acid itself, as formed by NO X hydrolysis, is known to increase the dew point only insignificantly . Contrary to nitric acid however, even traces of sulfuric acid, as a result of the sulfur content of the fuel gases (typically 14 mg normalmSTP3 H 2 S), are able to raise the acid dew point of the diffusing gas mixture well over 100°C.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In this range of wall temperatures usual operating conditions would not produce water vapor condensation between outer steel casing and refractory bricks. In addition to pure water vapor, the nitric acid itself, as formed by NO X hydrolysis, is known to increase the dew point only insignificantly . Contrary to nitric acid however, even traces of sulfuric acid, as a result of the sulfur content of the fuel gases (typically 14 mg normalmSTP3 H 2 S), are able to raise the acid dew point of the diffusing gas mixture well over 100°C.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Naris Sridhar et al [10] reported that intergranular stress corrosion cracking (IG SCC) has generally not been observed when the pH greater than 11.0. According to potential pH or pourbaix diagram [11] dangerous zones where SCC caused by nitrate solution is between pH 2.2 and 5.2, with corresponding potential between 0-I000 mV SCE .…”
Section: Metallographic Examinationmentioning
confidence: 99%
“… SCC in nitrate environments. In condensing waste gases with high concentrations of NO 2 , nitric acid and nitrates are formed resulting in intergranular SCC (Leferink and Huijbregts, 2002). Mechanical failure.…”
Section: Database Of “Mild” Steelsmentioning
confidence: 99%
“…Parkins stated that stress corrosion cracking in nitrate environments starts with intergranular corrosion and that the “cracking” should be considered as strain‐assisted intergranular corrosion (Parkins, 1980). At KEMA laboratories, the resistance of several ferritic steels to intergranular corrosion in ammonium nitrate solutions was tested (Leferink and Huijbregts, 2002).…”
Section: Nitrate Intergranullar Corrosion (Nitrate Scc)mentioning
confidence: 99%